2020
DOI: 10.1002/bit.27518
|View full text |Cite
|
Sign up to set email alerts
|

Mining of UDP‐glucosyltrfansferases in licorice for controllable glycosylation of pentacyclic triterpenoids

Abstract: Pentacyclic triterpenoids have wide applications in the pharmaceutical industry. The precise glucosylation at C-3 OH of pentacyclic triterpenoids mediated by uridine 5'-diphospho-glucosyltransferase (UDP-glucosyltransferase [UGT]) is an important way to produce valuable derivatives with various improved functions. However, most reported UGTs suffer from low regiospecificity toward the OH and COOH groups of pentacyclic triterpenoids, which significantly decreases the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…Although systematic metabolic engineering strategies have been employed in the present study, the production of GA and GAMG was still much lower than other triterpenoids (include GA) reported previously ( Zhu et al, 2017 ; Zhuang et al, 2017 ; Wang C. et al, 2019 ; Zhang et al, 2020 ). The discrepancy in GA production might result from the use of yeast strains with different genetic backgrounds.…”
Section: Discussionmentioning
confidence: 64%
“…Although systematic metabolic engineering strategies have been employed in the present study, the production of GA and GAMG was still much lower than other triterpenoids (include GA) reported previously ( Zhu et al, 2017 ; Zhuang et al, 2017 ; Wang C. et al, 2019 ; Zhang et al, 2020 ). The discrepancy in GA production might result from the use of yeast strains with different genetic backgrounds.…”
Section: Discussionmentioning
confidence: 64%
“…Glycosyltransferase activity also affected glycoside compound production . In our study, Ugt73c6 and Ugt73b2, two glycosyltransferases, showed different catalytic abilities, with Ugt73C6 having a stronger catalytic ability in producing naringenin-7-O-glucoside from (2 S )-naringenin.…”
Section: Discussionmentioning
confidence: 65%
“…UGT73C11, 51,52 UGT73C33 and UGT73F24, 53 which had been reported to show activity toward pentacyclic triterpenoids, were first tested in vitro for the C-28 glucosylation of CE and/or OA. Unfortunately, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%